Bangla sign language recognition and sentence building using deep learning - Shurid, Safayet Anowar; Amin, Khandaker Habibul; Mirbahar, Md. Shahnawaz; Karmaker, Dolan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.